An Analytical Viewpoint of the Educational Perspectives of Karl Marx’s Communist Manifesto - Afzal, Ashfaq; Fatima Kashif, Mahvish; Munir, Hina (Pakistan Languages and Humanities Review, 2023)
The study was conducted to analyze the educational perspectives of communist manifesto. The objective of the study was exploring the role of education in promoting class inequality, determine the role of current education system towards providing equal opportunity for learners irrespective of their socio-economic status and identify role of education system in promoting obedience and the acceptance of hierarchy, which eventually reproduces capitalism. Everybody do not have an equal chance to continue their studies in our current education system, because in our education system, all that matters is how much money you have to continue your education. Instead of merit, people are getting selected for different roles on the basis of socio-economic status. Education is transmitting the ideology of ruling class. Additionally, education is replicating fresh families of labour who have been taught to accept their role in capitalist society, education promotes obedience.